Finite Element Analysis on All on Four Implant Screw Retained Mandibular Fixed Prosthesis. (Material Selection Role) - Salah A. Youssef; Mohammed Galal, Rami; Ghada E. Hamza; Ghith Fayez Saeed Aldhahri; Ahmad Ramzi Abdu Alzaylaei; Mohammed Saleh Mohammed Alamoudi; Abdullah Abdulrahman Ahmad Benjabi; Yousef Hatem Jayar; Ammar Abdulrahim Abdulqahhar Khoja; Ahmad Mohammad Salem Alsaiary; et al. (International Journal of Innovative Research in Medical Science, 2020)
Aim: to indicate the importance of adequate selection of all on four-fixed implant supported hybrid mandibular prosthesis material to reduce bone stresses. Materials and methods: one three-dimensional simplified geometric model, for bone and fixed prosthesis, was created by using engineering CAD/CAM software. On the other hand, implant system manufacturer data gave sufficient geometrical data to model it exactly. The modelled part was transferred to ANSYS for assembly, meshing, and analysis. Three overlying materials were tested; Acrylic, Polycarbonate, and Zirconia above the cobalt chromium bar. The lowest area of the cortical bone was set to be fixed in place as boundary condition. While unilaterally load of 250N was applied vertically on central fossa of first and second molars as two loading cases. Results: changing overlying material resulted in, cortical bone and implant complex receiving Von Mises stress in sequence with material rigidity. The more rigid the overlying material the less bone stresses with first molar loading, while, opposite trend (sequence) appeared with second molar loading. On the other hand, bar, coping, screws, mucosa, and spongy bone deformations and stresses decreased with increasing overlying material rigidity. Where, all the model components showed stresses and deformations within the physiological limits. Conclusions: More rigid overlying material is recommended to reduce stresses on bar, coping, screws, mucosa, and spongy bone. Overlying material selection for cortical bone and implant complex is extremely tricky. That it showed same behaviour as other soft tissues with applying load close to the bar (short cantilever arm), then inverted behaviour with shifting the applied load away from first to second molar (increasing cantilever arm).